Campus Greening, Property Aesthetics, and Learners’ Comfort: The Case of Adeleke University, Ede, Nigeria - Ankeli, I. A.; Lawal, M. O. (International Journal of Real Estate, 2025)
The significance of greening our campuses and enhancing their scenic beauty is increasingly recognized as vital for supporting student well-being, boosting academic engagement, enhancing property aesthetics and shaping institutional identity. This research sets out to explore how property, greening aesthetic appeal, and student comfort interact at Adeleke University, Ede, Nigeria. The study employed a mixed-methods research approach, utilizing structured questionnaires, field observations, and in-depth interviews to gather insights into students’ perceptions and experiences of their campus environment. The results indicate that property aesthetics, green spaces and visually appealing areas significantly improve students’ psychological comfort, sense of belonging, and overall satisfaction with their academic surroundings. Moreover, well-kept greenery, shaded spots, and artistic sculptures contribute to students’ relaxation, stress relief, and cognitive focus. This research highlights the importance of intentional landscape design and ecological care in fostering effective educational settings. It advocates for the strategic development of campuses as living laboratories and sustainable greening initiatives to strengthen the connection between built environments and nature.